Payments for environmental services in Costa Rica: increasing efficiency through spatial differentiation - Wunscher, T.; Engel, S.; Wunder, Sven (2006)
Costa Rica was the first developing country to have implemented a nation-wide program of payments for environmental services. We analyze whether the efficiency of the program could be increased through better targeting techniques and propose a targeting mechanism which takes into account the spatial diversity of service provision and opportunity cost. Given a fixed budget we show that selecting sites according to their service delivery potential increases the amount of contracted services. The efficiency increase is even more pronounced when opportunity costs are taken into account and payment levels are varied accordingly. We also observe that the use of the above mentioned concepts decreases the average area of the selected, sites which might indicate that the proposed approaches encourage participation of the poor.